Legal risk in bank compensation: A look at the Banking Law and the positions of Indecopi and the Judiciary - Pineda Galarza, Jhon (2025)
The financial system regulation establishes mechanisms to protect the public savings, required by the Peruvian Political Constitution. One ofthose mechanisms is the “Netting”. However, in the last 15 years, Indecopi has issued resolutions preventing the application of this provision; andamong some years, there have been pronouncements from the Judiciary Entity, that include in their analysis the constitutional protection of salary.